International Society of Cardiovascular Infectious Diseases Guidelines for the Diagnosis, Treatment and Prevention of Disseminated Mycobacterium chimaera Infection Following Cardiac Surgery with Cardiopulmonary Bypass. Issue 2 (February 2020) - ,; ,; ,; ,; ,; ,; ,; ,; ,; Baddour, L.M.; Diekema, D.; Fernández-Hidalgo, N.; et al.
Summary: Mycobacterial infection-related morbidity and mortality in patients following cardiopulmonary bypass surgery is high and there is a growing need for a consensus-based expert opinion to provide international guidance for diagnosing, preventing and treating in these patients. In this document the International Society for Cardiovascular Infectious Diseases (ISCVID) covers aspects of prevention (field of hospital epidemiology), clinical management (infectious disease specialists, cardiac surgeons, ophthalmologists, others), laboratory diagnostics (microbiologists, molecular diagnostics), device management (perfusionists, cardiac surgeons) and public health aspects.